Prospective evaluation of lymphatic embolization as part of the treatment in dogs with presumptive idiopathic chylothorax. (12th June 2022) - Carvajal, Jose L.; Case, J. Brad; Vilaplana Grosso, Federico R.; Fox‐Alvarez, William A.; Regier, Penny J.; Verpaalen, Valentine; Toskich, Beau B.
Abstract: Objective: To describe the embolization technique and short‐term clinical outcome in dogs undergoing lymphatic embolization (LE) as part of treatment for presumptive idiopathic chylothorax (IC). Additionally, to document findings in computed tomography lymphangiography (CTLa) following embolization. Study design: Prospective case series. Animals: Eight client‐owned dogs. Methods: Dogs underwent CTLa followed by thoracic duct ligation (TDL), pericardiectomy (PC) and LE. A mixture of 3:1 lipiodol: n ‐butyl cyanoacrylate embolic solution was injected through a catheterized mesenteric lymphatic vessel via limited abdominal approach using intraoperative fluoroscopy. CTLa was scheduled for 12 weeks postoperatively, and long‐term follow‐up was obtained via telephone contact. Results: LE was technically successful in six of the eight dogs; and clinically successful in five of the six dogs. In the unsuccessful dog, a diagnosis of lymphangiosarcoma was determined, and the owners elected for euthanasia. Five dogs who underwent successful LE underwent CTLa at 12 weeks. Complete resolution of pleural effusion occurred in three dogs and scant pleural effusion in two dogs. A robust lymphatic embolus preventing antegrade continuation of radiocontrast was documented in all five dogs. Five of the six dogs that underwent LE, were alive and clinically normal at 358–960 days postoperatively. Conclusions: LE is a feasible part of treatment for dogs with IC. Additionally, a robust lymphatic embolus and lack of radiocontrast flow past the embolus was documented at 12 weeks following surgery. Clinical significance: LE has the potential to reduce surgical failure by reducing efferent lymphatic chyle flow, occluding missed lymphatic branches and preventing the development of collateral branches.